Glioblastoma multiforme - disease overview considering sports and neurorehabilitation - Niedźwiedzka, Monika; Rosińska, Kamila; Łojewska, Julia Natalia; Janicka, Ewelina Justyna; Perko, Agnieszka; Rosiński, Mateusz; Mocarska-Aniśko, Marta (Quality in Sport, 2024)
The brain is the most important organ, coordinating the work of the entire body. However, even it sometimes makes mistakes. Mutations in its genetic material can lead to the development of one of the most aggressive cancers - glioblastoma multiforme. Glioblastoma multiforme is the most common primary malignant tumor of the central nervous system (CNS). According to the WHO, it is classified as grade 4 in terms of malignancy. The 5-year survival rate is 7.2%. Occurs worldwide with a frequency of less than 10 cases per 100,000 inhabitants. It is more common in men than in women, with an average age at diagnosis of 65 years. The primary confirmed risk factor is exposure to ionizing radiation. Despite advances in medical research, the prognosis for individuals with glioblastoma multiforme remains unfavorable. The median survival time remains around 15 months. This article provides an overview of glioblastoma multiforme, including its etiology, symptoms, diagnosis, and treatment. By elucidating the current state of knowledge on glioblastoma multiforme, this work aims to facilitate early detection, treatment, and raise awareness among both physicians and patients about the disease. [7,14,17]